2015
DOI: 10.1002/masy.201400018
|View full text |Cite
|
Sign up to set email alerts
|

Cationic Zirconocene‐Mediated Catalytic H‐Shuttling Polymerization of Polar Vinyl Monomers: Scopes of Catalyst, Chain‐Transfer Agent, and Monomer

Abstract: Summary: This study investigates the characteristics of the recently developed catalytic H-shuttling polymerization (HSP) of polar vinyl monomers mediated by cationic zirconocenium catalysts, through examining the scopes of chain transfer agent, catalyst, and monomer. Amongst the three classes of chain transfer agents (metal hydrides, metal aryl/alkyls, organics) investigated for the MMA polymerization catalyzed by C s -ligated catalyst 1, the Lewis acid B(C 6 F 5 ) 3 , metal hydrides MH (M ¼ K, Na, Li) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It has been well established that coordination–addition polymerization of polar vinyl monomers by cationic zirconocenium catalysts occurs through a labile eight-membered-ring chelate intermediate (resting state, exemplified by B in Scheme ) formed upon Michael addition of the growing ester enolate chain end onto the conjugated CC of the incoming monomer (active species, exemplified by A in Scheme ). , ,,,, Moreover, it has been determined that the ring opening of the resting state to accommodate the coordination of the new incoming monomer is the rate-determining step (rds) of the polymerization reaction. In this work, we have shown that DMIA, D i PrIA, and MMA were not capable of ring opening the eight- and seven-membered-ring chelate complexes formed after the first monomer addition took place, effectively prohibiting the polymerization reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It has been well established that coordination–addition polymerization of polar vinyl monomers by cationic zirconocenium catalysts occurs through a labile eight-membered-ring chelate intermediate (resting state, exemplified by B in Scheme ) formed upon Michael addition of the growing ester enolate chain end onto the conjugated CC of the incoming monomer (active species, exemplified by A in Scheme ). , ,,,, Moreover, it has been determined that the ring opening of the resting state to accommodate the coordination of the new incoming monomer is the rate-determining step (rds) of the polymerization reaction. In this work, we have shown that DMIA, D i PrIA, and MMA were not capable of ring opening the eight- and seven-membered-ring chelate complexes formed after the first monomer addition took place, effectively prohibiting the polymerization reaction.…”
Section: Resultsmentioning
confidence: 99%